2015
DOI: 10.1186/s12937-016-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on nutrient intake and -status in inflammatory bowel disease patients

Abstract: Background and aimsInflammatory bowel disease (IBD) can be associated with nutritional problems. The aim of this study was to investigate diet and nutritional status of IBD patients.MethodsA total of 78 participants (35 men and 43 women aged 18–74 years) were included in this cross-sectional study. The majority (80 %) of the participant received infliximab treatment. Participants filled out disease related questionnaires and 31 participants also a 3-day food record. Body composition was measured and blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 26 publications
7
58
2
2
Order By: Relevance
“…In our study, 38% of the IBD patients claimed to have changed their diet, mostly because of gastrointestinal afflictions including indigestions, bowel complaints or stomach pain. This percentage is much lower compared to a recent study of Vidarsdottir et al, where 87% of the IBD patients were convinced that the food affects their gastrointestinal tract; 72% of these patients changed their diet during the course of the disease [34]. This discrepancy with our data may be caused by the fact that we asked for dietary changes only within in the past twelve months, but the actual disease duration of our IBD patients ranged from six months up to 54 years.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…In our study, 38% of the IBD patients claimed to have changed their diet, mostly because of gastrointestinal afflictions including indigestions, bowel complaints or stomach pain. This percentage is much lower compared to a recent study of Vidarsdottir et al, where 87% of the IBD patients were convinced that the food affects their gastrointestinal tract; 72% of these patients changed their diet during the course of the disease [34]. This discrepancy with our data may be caused by the fact that we asked for dietary changes only within in the past twelve months, but the actual disease duration of our IBD patients ranged from six months up to 54 years.…”
Section: Discussioncontrasting
confidence: 55%
“…The use of other alternative supplements like fish oil, cranberry extracts or St. John's wort was scarce. A recent study showed a similar prevalence for the use of vitamin and mineral supplements [34], with 27% of IBD patients consuming multivitamins compounds. Summarizing the use of vitamins (6%), minerals (4%) and combinations (15%) of the IBD patients in our study the prevalence was 25% and confirmed former results.…”
Section: Food Group Hc Total Ibd Ibd (Intake In [G/d]) CD Ucmentioning
confidence: 88%
See 3 more Smart Citations